SUPPLY CHAIN IN DIGITAL ERA: ROLE OF IT INFRASTRUCTURE AND TRADE DIGITALIZATION IN ENHANCING SUPPLY CHAIN PERFORMANCE - Saengchai, Sakapas; Jermsittiparsert, Kittisak (International Journal of Supply Chain Management, 2019)
Digitalization is knocking at the door of all industries but manufacturing industry is responding comparatively lesser than the other sectors. Poor IT infrastructure can lead towards diminishing performance at all fronts including financial, operational, marketing and supply chain. Trade digitalization can emerge as a savior in industry digitalization era. This study is focused to analyze the influence of IT standardization and integration on supply chain performance in mediating role of trade digitalization. Questionnaire-based survey was conducted in Thailandâ??s manufacturing industry where almost 47 firmsâ?? employees were taken as sample and their responses were analyzed on SPSS and AMOS for statistical findings. Findings have revealed that both dimensions of IT infrastructure have significant impact on supply chain performance and mediating role of trade digitalization was also flagged significant. None of the previous studies had checked trade digitalizationâ??s mediating role in respective relationship which was the originality of this study. Study has its implications for academia, industry and government as IT infrastructure has to be developed in not only Thailandâ??s industry but in all countries locating at Asian belt to enhance supply chain performance.